Kardiochirurgia dorosłych Long-term heart remodelling after surgical ablation for atrial fibrillation – 4-year long changes of left atrial transport function and N-terminated brain natriuretic propeptide (NT-proBNP) - Suwalski, Grzegorz; Suwalski, Piotr; Śledź, Mariusz; Scisło, Piotr; Kochanowski, Janusz; Witkowska, Anna; Popiel, Zbigniew; Kuriata, Jarosław; Wilimski, Radosław; Majstrak, Franciszek; Suwalski, Kazimierz B. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Long-term effectiveness of surgical atrial fibrillation (AF) ablation is high. Still few data on long-term atrial remodelling supporting transport function and heart failure reduction are available. Aim: Aim was to assess long-term changes of left atrium ejection fraction (LAEF) and NT-proBNP level in 4-year long follow-up after ablation. Material and Methods: 84 patients (mean age: 64.4±9.8 years) who underwent concomitant surgical ablation AF were included. At 3, 6, 12, 24, 48 months LAEF, NT-proBNP serum parameters and 24-hour Holter ECG were evaluated. If any electrocardiographically confirmed incidence of AF occurred at any time point the patient was qualified to the AF group. Results: 64 (76%) patients remained in SR during the observation period. Average LAEF was higher in SR than in AF patients, respectively: 31.6 (±10.6) vs. 24.6 (±7.2) %, p=0.007. In the AF group higher NT-proBNP levels were recorded after 24 months (782±471 vs. 357.6±319 pg/ml in the SR group; p=0.006) and 48 months (1531±650 vs. 456.6±182 pg/dl in SR patients; p=0.03). Between SR and AF patients there was no significant difference in preoperative left atrium diameter (respectively, 55±11 vs. 59±16 mm; p=0.2) and arrhythmia duration (respectively, 5.1±5.4 vs. 4.49±3.86 years; p=0.6). Conclusions: Long-term stable sinus rhythm maintenance after surgical ablation is related to significantly better LAEF and lower NT-proBNP level in comparison to patients with arrhythmia recurrence.